2016
DOI: 10.1017/s0007114516002245
|View full text |Cite
|
Sign up to set email alerts
|

ProbioticLactobacillus gasseriSBT2055 improves glucose tolerance and reduces body weight gain in rats by stimulating energy expenditure

Abstract: Probiotic Lactobacillus gasseri SBT2055 (LG2055) reduces postprandial TAG absorption and exerts anti-obesity effects in rats and humans; however, the underlying mechanisms are not fully understood. In the present study, we addressed the mechanistic insights of the anti-obesity activity of LG2055 by feeding Sprague-Dawley rats diets containing skimmed milk fermented or not by LG2055 for 4 weeks and by analysing energy expenditure, glucose tolerance, the levels of SCFA in the caecum and serum inflammatory marker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 56 publications
1
43
0
Order By: Relevance
“…LDA showed that probiotic treatments produced an increase in SCFA‐producing bacteria as the genera Odoribacter and Lachnospira . SCFAs are known to exert beneficial metabolic effects, improving insulin sensitivity through the enhancement of fat oxidation and energy expenditure . In fact, synbiotic1‐synbiotic2 treatment showed an increase in the family Porphyromonadaceae and one of its genera, Odoribacter .…”
Section: Discussionmentioning
confidence: 99%
“…LDA showed that probiotic treatments produced an increase in SCFA‐producing bacteria as the genera Odoribacter and Lachnospira . SCFAs are known to exert beneficial metabolic effects, improving insulin sensitivity through the enhancement of fat oxidation and energy expenditure . In fact, synbiotic1‐synbiotic2 treatment showed an increase in the family Porphyromonadaceae and one of its genera, Odoribacter .…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms to explain the relationship between Ruminococcaceae RA and markers of browning in SAT remain to be elucidated. Gut microbial‐derived SCFAs have been demonstrated to improve insulin sensitivity through the enhancing of fat oxidation and energy expenditure . Acetate seems to exert a crucial role in brown adipocyte differentiation through the induction of mitochondrial biogenesis, leading to increased oxygen consumption rate in white and brown adipocytes and skeletal muscle from Otsuka Long‐Evans Tokushima Fatty rats; and increased browning of SAT in parallel to increased insulin sensitivity in mice .…”
Section: Discussionmentioning
confidence: 99%
“…Milk fermented by LG2055 was prepared as described previously (Shirouchi et al, 2016). In addition, the chemical compositions of skim milk (SM) and LG2055 fermented SM powders were the same as described previously (Shirouchi et al, 2016). The final concentration of viable LG2055 in the fermented SM-containing diet was 6 × 10 7 cfu/g of diet.…”
Section: Preparation Of Milk Fermented By Lg2055mentioning
confidence: 99%
“…Experimental diets were prepared based on the AIN-76 formula (American Institute of Nutrition, 1977) with several modifications and contained (g/kg) 100 fat (90 lard and 10 corn oil), 200 nonfermented SM powder (control diet) or LG2055-fermented SM powder (LG2055 diet), 125 casein, 150 α-cornstarch, 50 cellulose, 3 dl-methionine, 35 mineral mixture (AIN-76), 10 vitamin mixture (AIN-76), 0.5 cholesterol, and 326.5 sucrose. The protein concentration of diets prepared using fermented and nonfermented SM was the same as described previously (Shirouchi et al, 2016). Diets containing high sucrose levels and lard rich in SFA were used to induce obesity and glucose intolerance.…”
Section: Animal Experimentsmentioning
confidence: 99%
See 1 more Smart Citation